Evaluasi Pasca Huni Pengguna Internal terhadap Performa Fisik Kamar Operasi - Kusumawati, Martika Intan; Hariyono, Widodo; Iswanta, Iswanta (Kes Mas: Jurnal Fakultas Kesehatan Masyarakat, 2017)
Background: RS PKU Muhammadiyah Gamping is a Class C Hospital with a capacity of 154 beds. Hospital operating rooms are the most rigorous, complex and require more investment than other functions. The operating room is specially designed to perform elective and cito surgical procedures. Method: Type of descriptive observational study. Population of all internal users of Operating Room. The sample size is 20 people. Results: The operating room is located on the fourth floor of the hospital facing the ICU chamber. The operating room has a building area of about 50.4x18 meters. The operating room has four operating rooms consisting of two large operating rooms, a small operating room, and a dedicated operating room equipped with c-arm neurosurgery. The operating room area I=6.3x6.3 meter, operating room area II=7.2x6.35 meter, operating room area III=7.2x6.35 meter, operating room area IV=7.2x7.2 meter. Lighting 348 lux operating room, 18.160 lux field operation lighting. Operating room humidity=44.3%. Operating room temperature=27.3oC. Noise operating room=52.4dB. The pressure inside the operating room=1013.3 mBar equals the pressure in the corridor=1013.3 mBar. Airflow on the non-asprating diffuser over the operating table 0 ftm. Filterization shows the index of standard germs. Technical aspects are approaching the standard. The results of the functional and process aspects are not in accordance with the standards. Conclusion: Humidity, pressure, temperature, and noise levels are not in accordance with ministry of health of Republic Indonesisa standard in 2012, based on internal user perception of technical aspect is approaching standard, while functional aspect and process are considered not in accordance with standard.